SOURCES THAT MANAGERS PREFER FOR BUSINESS INFORMATION NEEDS - Çiğdem Baskıcı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi, 2019)
This study aims to reveal how business managersassociate their information needs and the information sources to meet theseneeds. In order to answer this question, face-to-face interviews were carriedout with a total of 327 business managers working in various sectors.Information sources are encoded by using content analysis with personal andnon-personal, internal and external dimensions. Results obtained have shownthat managers mainly prefer non-personal information sources. Accordingly,business managers who face problems of sustainability and competitiveness seekpersonal and internal information while those who face problems of growth andinnovation seek non-personal and external information. As for the problemprofitability, managers refer to non-personal and internal information. Thefindings aim to contribute to strategic management and environmental scanningliterature as well as to implementers. The research results might be guidingfor identifying the information needs of managers in a more focused way andmeeting this need more efficiently.